Swing Suppression Task in Double-pendulum Tower Cranes Using Robust Adaptive Sliding Mode Controller. Issue 1 (1st March 2022) - Tian, Zheng; Ouyang, Huimin; Yu, Lili
Abstract: In actual applications, tower crane systems are usually suffered from underactuated characteristic, double-pendulum effect, frictions, model uncertainties and disturbances etc. As a result of these problems, the control of tower cranes for accurate positioning and effective swing suppression becomes more difficult. To this end, we propose a robust adaptive sliding mode controller, which has adaptive gains varying by the system tracking error and adaptive terms to compensate the lumped disturbances in all DOF (degrees of freedom). Therefore, the system convergence rate is effectively increased and the disturbances-related factors are suppressed. Simulation results show that the proposed method can handle the actual conditions better.